2021
DOI: 10.5194/ms-12-31-2021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of influence factors of rail corrugation in small radius curve track

Abstract: Abstract. In order to effectively prevent and control the generation and development of rail corrugation, according to the actual line condition of the small radius curve section, the vehicle (with flexible wheel sets)–track space coupled model was established by using the multi-body dynamic software UM (Universal Mechanism), which could consider the coupled relationship in three directions of space, and the dynamic analysis for the corrugation section was carried out by using the model. Then, based on the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Well-maintained tracks reduce friction and allow smoother operation, which in turn reduces energy consumption. Similarly, regular maintenance of trains, including component cleaning and lubrication, ensures they operate efficiently, avoiding energy waste and unnecessary emissions [54][55][56][57].…”
Section: Carbon Emission Characteristics Of Railwaysmentioning
confidence: 99%
“…Well-maintained tracks reduce friction and allow smoother operation, which in turn reduces energy consumption. Similarly, regular maintenance of trains, including component cleaning and lubrication, ensures they operate efficiently, avoiding energy waste and unnecessary emissions [54][55][56][57].…”
Section: Carbon Emission Characteristics Of Railwaysmentioning
confidence: 99%
“…Wang and Lei [22] also studied the stick-slip characteristics of wheel-rail contact under different super, standard, and high conditions and found that both the inner and outer wheel-rail systems had the possibility of a stick-slip movement on the small-radius curve of the subway, and the inner wheel-rail system was more likely to cause the formation of rail corrugation. In terms of other research methods, Wang and Lei [21] used the three-dimensional finite-element model of a wheel-rail system to carry out the complex eigenvalue analysis of influence factors for corrugation. In this study, it is found that in order to increase the stability of the wheel-rail system and suppress its unstable vibration, it is necessary to maintain the balanced superelevation of the track structure, which can play a critical role in suppressing the corrugation of the rail.…”
Section: Formation Mechanismsmentioning
confidence: 99%
“…A spring-damping element is used to simulate the fastener to realize the connection between the rail and the slab. In terms of other research methods, Wang and Lei [21] used the three-dimensional finite-element model of a wheel-rail system to carry out the complex eigenvalue analysis of influence factors for corrugation. In this study, it is found that in order to increase the stability of the wheel-rail system and suppress its unstable vibration, it is necessary to maintain the balanced superelevation of the track structure, which can play a critical role in suppressing the corrugation of the rail.…”
Section: Formation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fastener spacing is 0.6 m and the wheel-rail coefficient of friction is 0.35. The vertical force F v of axle box is calculated by the dynamics software UM (Universal Mechanism) [20]. Firstly, the vehicle-track coupling model is constructed according to the actual line situation, and then the vertical force of axle box when the vehicle passes through the target line section is obtained through simulation, and its value is 69 000 N. The wheel-rail longitudinal relative slip is set as 65.42 mm [21].…”
Section: Model Parametersmentioning
confidence: 99%